Prevalence of some internal diseases depending on the adipokine level in people under 45 years of age - E. V. Kashtanova; Ya. V. Polonskaya; L. V. Shcherbakova; V. S. Shramko; E. M. Stakhneva; A. D. Khudyakova; E. V. Sadovski; D. V. Denisova; Yu. I. Ragino (Бюллетень сибирской медицины, 2024)
The aim was to study the prevalence of some common internal diseases in young people of working and childbearing age, depending on the levels of adipokines.Materials and methods. The study included 1,340 people aged 25–44 years. The levels of leptin, adiponectin, adipsin, lipocalin-2, plasminogen activator inhibitor-1 (PAI-1), and resistin were determined by the multiplex analysis. Low-density lipoprotein hypercholesterolemia (LDL hypercholesterolemia), coronary artery disease (CAD), type 2 diabetes mellitus (T2DM), arterial hypertension (AH), renal dysfunction (RD), and chronic bronchitis (CB) were studied.Results. With an increase in the level of adiponectin, the prevalence of CAD increased by 8.6 times. The highest quartile of the adipsin level was characterized by an increase in the prevalence of LDL hypercholesterolemia by 12.9%, AH by 3.9%, and RD by 17.9%. The quartiles of lipolkalin-2 showed higher prevalence of LDL hypercholesterolemia, AH, and RD in Q4 compared to Q1. The prevalence of CB was associated with a decrease in the level of lipocalin-2 and was higher by 35.9% within Q1 compared to Q4. In the quartiles of PAI-1, the prevalence of T2DM and LDL hypercholesterolemia was 2 and 1.5 times higher, respectively, and the prevalence of RD was 2.5 times lower in Q4 than in Q1. In quartiles of resistin, the prevalence of LDL hypercholesterolemia, AH, and RD increased by 13–38%, while the prevalence of CB decreased by 20% in Q4, compared to Q1. The prevalence of LDL hypercholesterolemia and RD was higher within Q4 of leptin.Conclusion. The results indicate the need for further research aimed at studying the molecular mechanisms underlying the effects of adipokines. This will allow to find a combined approach to restoring normal physiological levels of adipokines, which can have a positive effect in the studied internal diseases.